Connectivity Without Proximity: Technoconferencing and the Transformation of Family Communication in the Gadget Era - Muhammad Dalim; Rubino; Lely Diana Fitri (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: To examine how gadget use creates technoference and reshapes family communication, emphasizing the quality of attention and presence rather than screen time. Theoretical framework: Combines family communication, family systems, technology domestication, parental mediation, and attention economy theories to explain technoference and phubbing. Literature review: Prior studies link gadget use to lower responsiveness and relationship quality, but also acknowledge its benefits for coordination and support. Most research still relies on screen-time measures and cross-sectional designs. Methods: This study employed qualitative methods through a structured literature review and thematic synthesis. Searches were conducted in Scopus, Web of Science, PubMed, and Google Scholar using a combination of the terms technoference, parental phubbing, family communication, smartphone, parent–child interaction, and digital parenting. Publications were analyzed through coding of meaning units, theme clustering, cross-design comparison, and conceptual interpretation. Results: The synthesis yielded five main themes: fragmentation of attention and loss of engagement cues; decreased responsiveness and emotional validation; conflict circulation and modeling of digital behavior; the ambivalence of gadgets as both connectors and barriers; and boundary negotiation as a means of managing family communication. The findings suggest that gadget consequences are not inherent to the device or determined solely by duration. Their impact depends on the relational value of a moment, the degree of distraction, the purpose of the activity, the clarity of the rules, and the interpretations of family members. Implications: This study shifts the focus from screen time to communication quality, emphasizing participatory family rules, gadget-free routines, parental role modeling, and digital literacy. Novelty: The KABAT model (Context, Attention, Boundaries, Activities, and Interpretations) explains how gadgets shape family communication by focusing on communication episodes rather than devices, providing a framework for future longitudinal and cross-cultural research.